A phosphokinome‐based screen uncovers new drug synergies for cancer driven by liver‐specific gain of nononcogenic receptor tyrosine kinases. Issue 5 (29th September 2017) - Fan, Yannan; Arechederra, Maria; Richelme, Sylvie; Daian, Fabrice; Novello, Chiara; Calderaro, Julien; Di Tommaso, Luca; Morcrette, Guillaume; Rebouissou, Sandra; Donadon, Matteo; Morenghi, Emanuela; Zucman‐Rossi, Jessica; et al.
Abstract : Genetic mutations leading to oncogenic variants of receptor tyrosine kinases (RTKs) are frequent events during tumorigenesis; however, the cellular vulnerability to nononcogenic RTK fluctuations has not been characterized. Here, we demonstrated genetically that in the liver subtle increases in wild‐type Met RTK levels are sufficient for spontaneous tumors in mice ( Alb‐R26 Met ), conceptually illustrating how the shift from physiological to pathological conditions results from slight perturbations in signaling dosage. By analyzing 96 different genes in a panel of tumor samples, we demonstrated that liver tumorigenesis modeled by Alb‐R26 Met mice corresponds to a subset of hepatocellular carcinoma (HCC) patients, thus establishing the clinical relevance of this HCC mouse model. We elucidated the regulatory networks underlying tumorigenesis by combining a phosphokinome screen with bioinformatics analysis. We then used the signaling diversity results obtained from Alb‐R26 Met HCC versus control livers to design an "educated guess" drug screen, which led to the identification of new, deleterious synthetic lethal interactions. In particular, we report synergistic effects of mitogen‐activated protein kinase kinase, ribosomal S6 kinase, and cyclin‐dependent kinase 1/2 in combination with Bcl‐XL inhibition on a panel of liver cancer cells. Focusing on mitogen‐activated protein kinase kinase and Bcl‐XL targeting, we mechanistically demonstrated concomitant down‐regulation of phosphorylated extracellular signal–regulated kinase and myeloid cell leukemia 1 levels. Of note, a phosphorylated extracellular signal–regulated kinase+/BCL‐XL + /myeloid cell leukemia 1+ signature, deregulated in Alb‐R26 Met tumors, characterizes a subgroup of HCC patients with poor prognosis. Conclusion: Our genetic studies highlight the heightened vulnerability of liver cells to subtle changes in nononcogenic RTK levels, allowing them to acquire a molecular profile that facilitates the full tumorigenic program; furthermore, our outcomes uncover new synthetic lethal interactions as potential therapies for a cluster of HCC patients. (Hepatology 2017;66:1644–1661).